Acute and chronic improvement in postprandial glucose metabolism by a diet resembling the traditional Mediterranean dietary pattern: Can SCFAs play a role?. Issue 2 (February 2021) - Vitale, Marilena; Giacco, Rosalba; Laiola, Manolo; Della Pepa, Giuseppe; Luongo, Delia; Mangione, Anna; Salamone, Dominic; Vitaglione, Paola; Ercolini, Danilo; Rivellese, Angela Albarosa
Summary: Background & aims: Postprandial metabolic abnormalities are considered important and independent risk factors for cardiovascular diseases. However, the effects of the Mediterranean diet on postprandial metabolism and the mechanism underpinning the effects on clinical variables have not been exhaustively explored. Therefore, the aims of the present study were to evaluate the acute and medium-term effects (8 weeks) on postprandial glucose and lipid metabolism of a diet resembling a typical Mediterranean diet (Med-D) compared to a western-type diet (Control-D), and the mechanisms underlying those effects. Methods: Twenty-nine overweight/obese individuals of both genders, aged 20–60 years, were enrolled and randomly assigned to two isoenergetic dietary interventions: 1) a Med-D (n = 16), and 2) a Control-D (n = 13). Adherence to the dietary interventions was assessed by a 7-day food record. A meal test resembling the assigned diet was performed at baseline and after 8 weeks of intervention. Blood samples at fasting and over 4-h after the meal were collected to assess metabolic parameters and short chain fatty acid (SCFA) levels. Fecal samples were also collected to evaluate the microbiota composition. Results: Glucose and insulin responses were significantly reduced at baseline after the Med test meal compared to the Control meal (p < 0.05) and this effect was strengthened after 8 weeks of intervention with the Mediterranean diet (p < 0.05); together with an improvement in OGIS. At the end of the intervention, postprandial plasma butyric acid incremental area under the curve (IAUC) was significantly increased in the Med-D group (p = 0.019) and correlated inversely with plasma insulin IAUC and directly with oral glucose insulin sensitivity (OGIS) (r: −0.411, p = 0.046 and r: 0.397, p = 0.050 respectively). These metabolic changes were accompanied by significant changes in gut microbiota, such as an increase in the relative abundance of Intestinimonas butyriciproducens and Akkermansia muciniphila (p < 0.05) in the Med-D compared to Control-D group. Conclusions: Our study provides strong evidence that a diet resembling the traditional Med-D improves postprandial glucose metabolism and insulin sensitivity. Furthermore, the study highlights a possible involvement of gut microbiota metabolites - such as butyric acid, and of dietary fiber as a precursor - in improving glucose metabolism and insulin sensitivity.